Association Between Serum Apolipoprotein B and Bone Mineral Density and the Effects of Cardiovascular Disease Mediation: Results From the NHANES 2011–2016 and a Mendelian Randomization Study - Aochuan Sun; Yiduo Chen; Yang Wu; Zhuangzhuang Li; Jingchun Zhang; Zhengtang Liu (Reviews in Cardiovascular Medicine)
Background: Previous studies have indicated that blood lipids can influence skeletal health. However, limited research exists on the impact of serum apolipoprotein B (ApoB) on bone mineral density (BMD); meanwhile, it remains unclear to what extent cardiovascular disease plays in mediating this process. Methods: Therefore, we conducted a cross-sectional analysis involving 2930 participants from the National Health and Nutrition Examination Survey (NHANES) database to explore the relationship between serum ApoB and total body BMD (TB-BMD) and lumbar spine BMD (LS-BMD). We employed a two-step, two-sample Mendelian randomization (MR) analysis using genetic instruments to investigate causality and assess the mediating effects of six cardiovascular diseases. Results: Multivariable linear regression models demonstrated an inverse linear association between serum ApoB and TB-BMD (β = –0.26, 95% confidence interval (CI): –0.41 to –0.12, p < 0.001; p for non-linearity = 0.771) and LS-BMD (β = –0.53, 95% CI: –0.75 to –0.31, p < 0.001; p for non-linearity = 0.164). The primary analysis utilized the multiplicative random effects inverse variance weighted (IVW-MRE) method for the two-sample MR analysis. The results demonstrated a causal relationship between serum ApoB with TB-BMD (β = –0.0424, 95% CI: –0.0746 to –0.0103; p = 0.0096) and LS-BMD (β = –0.0806, 95% CI: –0.1384 to –0.0229; p = 0.0062). The two-step MR analysis indicated heart failure as a mediating factor in the causal relationship between serum ApoB and TB-BMD, with a mediation proportion of 18.69%. Conclusions: The results of this study support that lowering serum ApoB levels could enhance BMD while preventing the occurrence of heart failure might reduce the harm caused by the decrease in BMD due to elevated ApoB levels.